10.3928/08910162-20080701-01 (CrossRef Listing of Deleted DOIs, 2000)
Background Empathy is central to compassionate nursing care, yet teaching and measuring this skill, especially in online settings, remains challenging. Creative, arts-based assignments present an innovative and engaging approach to bridging this gap in nursing education. Method In a nonexperimental pilot program, 52 nurse practitioner students in a graduate-level Women's Health course completed a reflective empathy essay, selecting artistic works to connect with women's health conditions. Perceptions and outcomes were assessed via an anonymous postassignment survey (Likert scale and open-ended questions). Results Ninety-two percent of the students agreed the assignment improved their empathy, with most finding the creative activity enjoyable and relevant. Narrative responses reflected deeper engagement and personal insights, although some students struggled to choose a meaningful creative work. Overall, the assignment positively influenced students' perspectives on patient care. Conclusion Arts-based assignments show promise for nurturing empathy in students. Future research should use validated empathy scales and expand curricular integration to confirm the effects of this pilot program.